Megathrust Shear Modulated by Albite Metasomatism in Subduction Mélanges - Kohtaro Ujiie; Kazuya Noro; Norio Shigematsu; Åke Fagereng; Naoki Nishiyama; Christopher J. Tulley; Haruna Masuyama; Yasushi Mori; Hiroyuki Kagi (Geochemistry, Geophysics, Geosystems)
Abstract Aseismic megathrust slip downdip of the seismogenic zone is accommodated by either steady creep or episodic slow slip events (SSEs). However, the geological conditions defining the rheology of megathrust slip remain elusive. We examined exhumed subduction mélanges on Kyushu, Japan, which deformed at ∼370–500°C under greenschist to epidote‐amphibolite facies conditions, comparable to warm‐slab environments. The mélanges recorded fluid release and viscous shear localization associated with metasomatic reactions between juxtaposed metapelitic and metabasaltic rocks. Metasomatic reactions caused albitization of metapelite, resulting in depth‐dependent changes to megathrust rheology. In a mélange deformed at ∼370°C, very fine grained reaction products (metasomatic albite) facilitated grain boundary diffusion creep at stresses of ∼45 MPa, less than those in the surrounding metabasalt. Mineralogical and chemical changes during metasomatic reactions, and their field content, imply an onset of albite metasomatism at ∼350°C. Albite metasomatism therefore potentially contributed to decreased megathrust strength around the inferred thermally controlled base of the seismogenic zone. In a mélange deformed near the mantle wedge corner at ∼500°C, metasomatic reactions promoted local quartz vein formation and localized viscous shear at slow slip strain rates, during which the coarse‐grained metasomatic albite behaved as relatively rigid blocks in a viscous matrix. We suggest that albite metasomatism can facilitate changes in a megathrust slip mode with depth and may explain why slip mode changes from creep to SSEs with tremor with increasing depth.